Where are Ecology and Biodiversity in Social–Ecological Systems Research? A Review of Research Methods and Applied Recommendations. Issue 1 (16th May 2016) - Rissman, Adena R.; Gillon, Sean
Abstract: Understanding social–ecological systems (SES) is critical for effective sustainability and biodiversity conservation initiatives. We systematically reviewed SES research to examine whether and how it integrates ecological and social domains and generates decision‐relevant recommendations. We aim to inform SES research methods and improve the relevance of SES research. Of 120 SES articles, two‐thirds included an ecological variable while all but one included a social variable. Biodiversity was a less common ecological variable than resource productivity, land cover, and abiotic measures. We found six diverse social–ecological linking methods: modeling (9%), causal loop diagrams (18%), quantitative correlations (8%), separate quantitative measures (13%), indicators (14%), and rich description (37%). Policy recommendations addressing social–ecological dynamics were more likely in articles including both ecological and social variables, suggesting the importance of research approach for policy and practice application. Further integration of ecology and biodiversity is needed to support governance, policy, and management for SES sustainability.